Gacha gotcha - Co, Kate Nicole M. (Animo Repository, 2022)
Gacha Gotcha is a vlog series about gacha game addiction that is divided into three (3) parts: the first video breaks down everything that is to know about gacha games and the elements that make them similar to gambling; the second video follows the story of two gacha game addicts who have spent a huge amount of money in different gacha games; and the last video summarizes important points made in the first two videos that also features the insights of the researcher regarding gacha game addiction. The sudden interest of people (both heavy gamers and casual gamers) in a gacha game called Genshin Impact piqued the interest of the proponent, which led her to investigate the elements of a gacha game that reels in people. As someone who used to play gacha games and was severely addicted to one of them, the proponent wanted to take a closer look into how gacha games work and find out what exactly makes them addictive and similar to gambling. The researcher conceptualized and developed the project, which was made by conducting virtual interviews with two game industry experts and two gacha game addicts via Zoom or Google Meet. Adobe Premiere Pro was used to make and edit the vlog series.1080p MP4 format, 3 videos.